Pre-Trial in Indonesia: Why it Should be Reformed - Faisal, Fitriah (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2023)
This study aims to find reasons why pretrial institutions are no longer relevant and must be immediately renew in Indonesian criminal procedural law. This article was compiled using the normative legal method. The study was conducted by examining the legislation, legal literature and doctrines related to pretrial. This study also uses three approaches, namely the statutory approach, the historical approach, and the conceptual approach. The results of the study show that pretrial reform in Indonesian criminal procedural law is important to be carried out immediately, Considering the many shortcomings that pre-trial institutions currently have, such as limited authority in the scope of the pre-adjudication stage which makes pre-trial far behind the models of similar institutions in various countries, and the absence of control or supervision over other crucial matters, such as determining whether evidence is obtained. in a legal way or not. Therefore, through the formation of a new criminal procedural law with pre-trial institutions changing their form to Commissioner Judges or Preliminary Examining Judges with a more active nature, it is hoped that human rights and citizen rights can be realized in the judicial process, as well as to achieve due process of law such as that is aspired to. The pros and cons of legal certainty and the principle of legality related to the decision of the constitutional court that expands the authority and broadly interprets several matters related to pretrial and criminal procedural law will be answered through the establishment or ratification of a new KUHAP with a pretrial institution that changes its form as a Commissioner Judge or Preliminary Examining Judge with more active nature.